Molecular docking studies on the interaction of anti-alzheimer compounds with amyloid beta peptides - Faujan, Nur Hana; Zakaria, Norzalina; Mohammad, Nurul Najihah (Bitlis, 2019)
Alzheimer’s disease is a neurodegenerative disorder. Aggregation of amyloid β-peptide (Aβ42) into fibrils is a key pathological process associated with Alzheimer’s disease. In this study, effect of surfactin against amyloid β-peptide was studied by using computational approaches. In the molecular docking, surfactin interacts with A chain of amyloid fibril and forms the hydrogen bonds with Ala 21 and Asp 23 with total energy of −3.28 kcal/mol. Surfactin interacts with an amphiphilic pore amyloid β-peptide (Aβ42); binding of surfactin to amyloid fiber shows the decrease in salt bridge length (between Asp 23 and Lys 28) from 11.5 to 9.0 Å; and this may lead to displace the water molecules and so destabilize the amyloid β-peptide (Aβ42). 10-ns molecular dynamics simulation was performed for amyloid fibril and with surfactin amyloid fibril complex. RMSD, RMSF, Rg trajectories, and SASA plot further used to study the stability of complex and effect of surfactin. This is the novel in silico study of surfactin against the amyloid β-peptide (Aβ42) fiber responsible for Alzheimer’s disease, and these results may provide an insight role of surfactin in the drug design against Alzheimer’s disease.